Pengaruh Environmental, Social and Governance (ESG) terhadap Nilai Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) pada tahun 2018-2022 - Indri Oktaviyana Sari; Sugeng Wahyudi (Diponegoro Journal of Management, 2025)
Sustainability issues involving environmental, social, and governance (ESG) aspects have gained global attention, particularly with the implementation of the Sustainable Development Goals (SDGs). In Indonesia, ESG reporting has become mandatory for public companies and financial institutions through POJK Regulation No. 51/POJK.03/2017. However, the understanding and implementation of ESG practices remain inconsistent, especially in the manufacturing sector, which plays a vital economic and environmental role. This study aims to examine the effect of ESG performance—both overall and by its components: environmental (ENV), social (SOC), and governance (GOV)—on the firm value of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Firm value is measured using Tobin’s Q ratio, and ESG scores are obtained from the Bloomberg Terminal. The sample consists of 115 companies selected through purposive sampling. The data were analysed using multiple linear regression and classical assumption tests. The findings indicate that the overall ESG score and leverage (DAR) have a significant positive effect on firm value. However, the individual ESG pillars show varied effects: the environmental and governance scores negatively affect firm value but are not significant, whereas the social score has a positive but insignificant effect. These results suggest that ESG’s influence on firm value is not uniform and highlight the need for improved ESG implementation in Indonesia.